2018
DOI: 10.1002/bit.26794
|View full text |Cite
|
Sign up to set email alerts
|

Control of amino acid transport into Chinese hamster ovary cells

Abstract: Amino acid transporters (AATs) represent a key interface between the cell and its environment, critical for all cellular processes: Energy generation, redox control, and synthesis of cell and product biomass. However, very little is known about the activity of different functional classes of AATs in Chinese hamster ovary (CHO) cells, how they support cell growth and productivity, and the potential for engineering their activity and/or the composition of amino acids in growth media to improve CHO cell performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 93 publications
1
13
0
Order By: Relevance
“…A pathway for oxidative stress was specifically designed so that the impact of high oxygen concentration in cell culture process is more accurately represented. This addition in the model makes (Geoghegan et al, 2018). Prediction of energy utilization and specific productivity could also be improved by considering the level of difficulty associated to the folding step of a specific antibody (Le Fourn et al, 2014), as well as the protein secretory pathway which has been identified as a bottleneck in some cases (Pieper et al, 2017;Rahimpour et al, 2013).…”
Section: Summary Of the Curation Processmentioning
confidence: 99%
“…A pathway for oxidative stress was specifically designed so that the impact of high oxygen concentration in cell culture process is more accurately represented. This addition in the model makes (Geoghegan et al, 2018). Prediction of energy utilization and specific productivity could also be improved by considering the level of difficulty associated to the folding step of a specific antibody (Le Fourn et al, 2014), as well as the protein secretory pathway which has been identified as a bottleneck in some cases (Pieper et al, 2017;Rahimpour et al, 2013).…”
Section: Summary Of the Curation Processmentioning
confidence: 99%
“…In addition, Geoghegan et al demonstrated that the mRNA expression of the cysteine transporter, xCT, was upregulated in CHO cells during increased mAb production in the stationary phase of growth. Moreover, this phenotype was sensitive to xCT inhibition by sulfasalazine and linked to oxidative stress induced by high mAb production (Geoghegan et al, 2018). These data taken together with data in this study, suggest that elevated xCT expression in the H 2 O 2 evolved host may be important for boosting BisAb titers and/or responding to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the transport capacity of the essential amino acids or inserting the complete pathways for their synthesis might be favourable for cell growth and protein production. Geoghegan et al identified amino acid transporters that are likely upregulated in producer cell lines and suggested that overexpression of one or more amino acid transporters might be beneficial for growth and productivity [178].…”
Section: Making Metabolism More Efficientmentioning
confidence: 99%